Pendampingan Legalitas UMKM PKH Graduasi Melalui Sistem Online Single Submission di Kecamatan Suruh - Nanang Adie Setyawan; Bagus Yunianto Wibowo; Lastri Sagita (Prapanca : Jurnal Abdimas, 2022)
Legal assistance regarding the Registration of Micro Small Business Permits in sub-districts is ordered through the Online Single Submission (OSS) System based on Government Regulation Number 24 of 2018, departing from the lack of socialization and education for PKH (Family Hope Program) Graduation SME’s actors. Implementation of community service in the form of micro, small and medium legal assistance to a number of 20 beneficiaries of the Family Hope Program. This community service aims to increase legal awareness of SME’s actors to take care of the legality of their business. Method of increasing legal awareness by providing assistance. The material for socialization includes Law no. 20 of 2008 concerning SME’s and Presidential Regulation No. 98 of 2014, Government Regulation Number 24 of 2018 concerning Integrated Electronic Business Licensing Services or (OSS). Micro, Small and Medium Enterprises as one of the actors of economic development in the regions need to be empowered through human resource development, capital support, production and productivity, business protection, partnership development, business networks and marketing as well as business legality through (OSS). ). The results of the mentoring show an increase in understanding and legal awareness of SME’s to take care of the legality of their business. Keywords: Mentoring, Legality, NIB (Business Permit Number), PKH Graduation